A note on the Helmert transformation. Issue 15 (30th June 2022) - Farhadian, Reza; Clarke, Brenton R.
Abstract: In this note, we consider a generalization of the well-known Helmert transformation. The main idea is that the proposed generalization allows us to obtain some new transformed normal variables for each original sample from N ( μ, σ 2 ) and N ( 0, 1 ) variates, such that, the Helmert transformation is a special case of them.